Assessing the Safety of Fish Retail Shops and Associated Environment for Antimicrobial Resistant Non–Typhoidal Salmonella - tripathi, maansi mani; S. Parveen; A. K. Upadhyay; R. Huozha (Fishery Technology, 2022)
Non-typhoidal salmonellosis stands among the major food illnesses. Outbreaks from contaminated fishes have been witnessed worldwide. A cross-sectional study was performed. A total of 368 samples (fish and associated environmental samples) were collected to assess the presence of non -typhoidal Salmonella in fishes and associated environment of 22 retail fish meat shops. The overall occurrence of the organismsÂ was found to be 4.35% (16/368) withÂ highest in rinsing water (18.18%,4/22) followed by knife swabs ( 11.11%, 3/27) , chopping board swabs (8.33%, 2/24) , meat swabs (6.52%, 3/46) , floor swab (4.54%,1/22) , gill and intestine swab (4.34%, 1/23), fish water (2.43%,1/41).Â S.Typhimurium (87.5%, 14/16) was found as the prevalent serovar.Â Major virulence genes harboredÂ were sipA gene (87.5%, 14/16) followed by stn (75%, 12/16), sopB ( 68.75%, 11/16), sopE1 ( 56.25%, 9/16) mgtC ( 43.75%, 7/16) and spvC and gipA ( 12.5%, 2/16) genes each. The isolates were highly resistantÂ against Tetracycline and Ampicillin (93.75%, 15/16) followed byÂ Nalidixic acid (50%, 8/16), Ciprofloxacin (37.5%, 6/16) Ofloxacin, Cefotaxime and Sulfisoxazole ( 25%, 4/16) each, Chloramphenicol (12.5%, 2/16) and Streptomycin ( 6.25%, 1/16). Ten Salmonella (62.5%) isolates were multi drug resistant (MDR). The most commonly occurring resistance gene was gyrA (92.30%, 12 /13), blaTEM (53.33%, 8/15), aadA1 and strA (50%, 2/4), sul1 (30.76 %, 4/13) while tetA was not found in any of the isolates. Resistance to critically important flouroquinolones and highly important Cephalosporin and Tetracycline antibiotic detected in Salmonella isolates is a serious threat to public health.